Anatomising Irish rebellion: the Cromwellian delinquency commissions, the books of discrimination and the 1641 depositions. Issue 157 (4th July 2016) - Cunningham, John
Abstract: The recent digitisation of the 1641 depositions has opened up that large and controversial collection of manuscripts to renewed study. The significance of a substantial section of that archive generated in 1653–4 by the work of the Cromwellian delinquency commissions has hitherto been poorly understood. This article sheds new light on the workings of the commissions and on the ways in which the 'delinquency depositions' that they collected helped to shape the implementation of the Cromwellian and Restoration land settlements in Ireland. It also compares the Irish delinquency proceedings to the approach adopted by the Long Parliament in its dealings with royalists in England in the 1640s. In analysing the actual content of the depositions, the article focuses particular attention on County Wexford. The surviving delinquency depositions enable in-depth exploration of many facets of the 1641 rebellion and its aftermath in that region.